2023
DOI: 10.1021/acscatal.2c05758
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Roles of Distinct Chemical Factors in the Hydrolytic Activities of Hetero- and Homonuclear Synthetic Analogues of Binuclear Metalloenzymes

Abstract: In this study, hydrolytic activities of hetero-and homobinuclear metallovariants of an asymmetric (I) or symmetric (II) ligand with the Fe III -Zn II , Zn II -Zn II , and Cu II -Cu II cores (i.e., I FZ , I ZZ , and I CC or II FZ , II ZZ , and II CC , respectively) are investigated using DFT calculations through four distinct mechanisms: dissociative (DA), substrate-assisted (SA), water-assisted (WA), and associative (AS). Additionally, the effects of different nucleophiles (μ-OH, terminal-OH, and -O 2 H 3 ), c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 179 publications
0
3
0
Order By: Relevance
“…224 However, as noticed above for other metal complexes, no Lewis acid activation of the substrate is observed and the catalyst-substrate interaction actually strengthens the scissile P-O bond by 0.04 Å in comparison to the corresponding bond in its free form. 227 That is in contrast to the activation of the scissile P-O bond of BNPP in the mechanisms utilized by GpdQ 210 and SgAP. 145 In an S N 2-type reaction, an in-line concerted attack of the Fe(III) bound hydroxyl nucleophile of FZ-I B on the electrophilic P atom of BDNPP leads to the cleavage of the scissile P-O bond with a barrier of 15.8 kcal mol À1 .…”
Section: Iid Synthetic Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…224 However, as noticed above for other metal complexes, no Lewis acid activation of the substrate is observed and the catalyst-substrate interaction actually strengthens the scissile P-O bond by 0.04 Å in comparison to the corresponding bond in its free form. 227 That is in contrast to the activation of the scissile P-O bond of BNPP in the mechanisms utilized by GpdQ 210 and SgAP. 145 In an S N 2-type reaction, an in-line concerted attack of the Fe(III) bound hydroxyl nucleophile of FZ-I B on the electrophilic P atom of BDNPP leads to the cleavage of the scissile P-O bond with a barrier of 15.8 kcal mol À1 .…”
Section: Iid Synthetic Analoguesmentioning
confidence: 99%
“…8b). 227 Here, Fe III is located in the N 2 O 2 site and Zn( ii ) in the N 3 O site. BDNPP is coordinated to the Zn( ii ) ion in a monodentate fashion which is supported by experimental data.…”
Section: Mechanisms Of Natural Metallohydrolases and Their Synthetic ...mentioning
confidence: 99%
“…By substituting the metal ion in vitro, it is observed that the enzyme demonstrates different mechanisms and activity. [37][38][39] This phenomenon is seen in various enzymes, such as glycerophosphodiesterase (GpdQ), 40,41 phosphotriesterase (PTE) from Pseudomonas diminuta, 42 and OP-degrading hydrolase from Agrobacterium radiobacter (OpdA). 43 Depending on the metal ion and ligand composition, these complexes adopt diverse geometries and electronic spin states.…”
Section: Introductionmentioning
confidence: 99%